1998
DOI: 10.1074/jbc.273.18.10851
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor Binding within the NarI Subunit (Cytochromeb nr) of Escherichia coli Nitrate Reductase A

Abstract: We have used inhibitors and site-directed mutants to investigate quinol binding to the cytochrome b nr (NarI) of Escherichia coli nitrate reductase (NarGHI). Both stigmatellin and 2-n-heptyl-4-hydroxyquinoline-N-oxide (HOQNO) inhibit menadiol:nitrate oxidoreductase activity with I 50 values of 0.25 and 6 M, respectively, and prevent the generation of a NarGHI-dependent proton electrochemical potential across the cytoplasmic membrane. These inhibitors have little effect on the rate of reduction of the two hemes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(93 citation statements)
references
References 37 publications
10
83
0
Order By: Relevance
“…It has been shown that the single point mutation of His-66 to tyrosine (H66Y) prevents the insertion of the heme b D as well as the binding of quinol analogs and inhibitors. Consequently, no quinol-dependent heme reduction is detected (7,9). However, in the NarGHI-PCP complex structure we present here the 13.2-Å edge-toedge distance between the heme b P and the bound PCP could still support electron transfer even in the absence of heme b D (32).…”
Section: Pcp Is a Potentmentioning
confidence: 71%
“…It has been shown that the single point mutation of His-66 to tyrosine (H66Y) prevents the insertion of the heme b D as well as the binding of quinol analogs and inhibitors. Consequently, no quinol-dependent heme reduction is detected (7,9). However, in the NarGHI-PCP complex structure we present here the 13.2-Å edge-toedge distance between the heme b P and the bound PCP could still support electron transfer even in the absence of heme b D (32).…”
Section: Pcp Is a Potentmentioning
confidence: 71%
“…First, it has been previously shown that the EPR spectrum of heme b D is exquisitely sensitive to the binding of the Q-site inhibitors 2-n-heptyl 4-hydroxyquinoline-N-oxide (HOQNO), pentachlorophenol (PCP), and stigma-tellin. 10,41 Herein, we show that binding of HOQNO collapses the heterogeneity in the heme b D EPR signal (Figure 3). Second, the heterogeneity is dependent upon growth conditions (Figure 2A), as are the membrane concentrations of menaquinone and ubiquinone.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a peak at g ϭ 2.92 is clearly resolved. This peak has been well characterized in NarI-enriched membranes and attributed to the b P heme in a relaxed NarI conformation occurring upon the absence of the NarGH dimer (16,17,28). The quantitation of the EPR signals associated to the b D heme shows that the proportion of this center is significantly higher than those of Moco and FS0 in ⌬1-41NarGHI (Table 2).…”
Section: Uncoupling Redox Cofactor Incorporation From the Membrane-anmentioning
confidence: 97%